Market politics and climate change - Harriss-White, B (2008)
Barbara Harriss-White argues that the structure and politics of national energy markets poses a major obstacle to finding and implementing solutions to the problem posed by climate change. Comparative research into these markets and their politics is urgently needed. She outlines some of the methodology needed for the effective study of markets, and proposes the UN give priority to encouraging such research and illustrates her argument with reference to a case study of the UK market for renewable energy.